2015
DOI: 10.2141/jpsa.0150046
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Various LED Light Colors on Growth and Immune Response in Broilers

Abstract: We evaluated the effects of different light-emitting diode (LED) colors between blue and green on growth performance and the immune response in broilers. A total of 1,200 1-day-old Ross broilers were divided randomly into six groups and exposed to pure blue (PB), bright blue (BB), sky blue (SB), greenish blue (GB), pure green (PG), or white (W) using LEDs for 6 weeks. Consequently, body weights were higher in chickens reared under PB and GB on day (d) 7 and SB on d 21 than the other groups. Chickens in the PB … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 21 publications
2
18
0
1
Order By: Relevance
“…Previous studies showed that continuous blue light does not affect food intake in chicks (Prayitno et al, 1997;Hassan et al, 2014;Seo et al, 2015). In the present study, chicks eat food under the blue light (Fig.…”
Section: Discussionsupporting
confidence: 59%
“…Previous studies showed that continuous blue light does not affect food intake in chicks (Prayitno et al, 1997;Hassan et al, 2014;Seo et al, 2015). In the present study, chicks eat food under the blue light (Fig.…”
Section: Discussionsupporting
confidence: 59%
“…The highest number of intestinal intraepithelial lymphocytes in broilers during the early growth stage was seen under green light, while numbers were highest under blue light during the late growth stage [138]. Similarly, green light showed the highest ConA-and LPS-induced lymphocyte proliferation in blood and spleen [140,141,144] and splenic IL-2 activity [141] during early growth stage, while at the end of the growth stage, blue light produced those same effects. Hassan et al [146] reported higher serum IgY and IgA concentrations under yellow light compared to white light, with no difference when comparing yellow or white light with green or blue light in the early growth stage.…”
Section: Light Color/wavelengthmentioning
confidence: 91%
“…Broilers reared under blue or green light compared to red light showed higher ConA-and LPS-induced lymphocyte proliferation in blood [139,140], spleen [141], bursa of Fabricius [142] and thymus [143]. Likewise, the activation of macrophages was higher under blue and green compared to white light [144]. Furthermore, chickens housed under green or blue light were also shown to have higher antibody titers after NDV vaccination [139,140,145] and higher total plasma or serum concentrations of IgY and IgA in broilers [146].…”
Section: Light Color/wavelengthmentioning
confidence: 94%
“…Cependant ils s'accordent pour affirmer que les lumières de courtes longueurs d'onde (perçues « bleues » et « vertes ») favorisent la croissance alors que les lumières de grandes longueurs d'onde (perçues rouges) favorisent la reproduction. Les poulets de chair soumis à une lumière « bleue » ont leurs fonctions immunitaires améliorées (Seo et al 2016) ainsi que la qualité gustative de leur chair (Ke et al 2011). Leur croissance est augmentée et particulièrement leur masse musculaire, en utilisant une lumière « verte » (Rozemboim et al 2013).…”
Section: L'animal De Rente : Un Animal-sentinelle D'un Environnement unclassified